The Odyssey Experience : Physical, Social, Psychological, and Spiritual Journeys. - Smelser, Neil J. (University of California Press, 2009)
This bold and innovative book traces the phenomenon of the "odyssey" experience as it shapes, informs, and defines our lives. Drawing on an astonishing range of examples, Neil J. Smelser focuses on how such experiences enhance our lives and provide us with meaning and dignity. The odyssey experience, as Smelser advances it, is generic, widespread, and recurring. It is a finite period of disengagement from the routines of life and immersion into a simpler, transitory, often collective, usually intense period of involvement that culminates in some kind of regeneration. By examining a variety of.